Species-Specific 18S rRNA Gene Amplification to Detect the Sequence Variation in Plasmodium Vivax Parasite - Rizwana Yasmin , Syeda Mariam , Mahadev Harani , Mehwish Kalam , Mumtaz Khan Muhammadee , Abid Ali Hashmi , Mustafa Kamal, Rizwana Yasmin , Syeda Mariam , Mahadev Harani , Mehwish Kalam , Mumtaz Khan Muhammadee , Abid Ali Hashmi , Mustafa Kamal (Journal of Rawalpindi Medical College, 2018)
Background:To ascertain species-specific 18S rRNA gene amplification, in order to detect the sequence variation in Plasmodium Vivax parasite. Methods: Blood samples from 150 suspected malaria cases were collected . Microscopically diagnosed cases of malaria were subjected to nested PCR amplification for genus and species confirmation. The 18S rRNA gene was amplified from 34 P.vivax positive cases. The obtained PCR products were subjected to sequence analysis, phylogenetic study and multiple sequence alignment. Results: The genus specific-positive malaria cases along with the mixed species done by nested PCR were 40.7 % (61 out of 150) while microscopy results revealed malaria positive cases to be 32.6 % (49 out of 150). The difference in detection of malaria parasite by PCR was more sensitive as compared to microscopy (two-tailed p.value = 0.0015).Among the nested PCR malaria-positive cases, P. vivax, was isolated in 55.7% (34 of 61) .Samples and P. falciparum were isolated in 34.4% (21 of 61) samples and mixed infection were detected in 9.8% (6 of 61) cases. While among the microscopy -positive malaria cases, P. vivax, was isolated in 57.1% (28 of 49) . P. falciparum were isolated in 32.7% (16 of 49) samples and mixed infection were detected in 10.2% (5 of 49) cases. Phylogenetic analysis and multiple alignment of the 18S rRNA was done on 13 selected cases of P.vivax isolates which revealed vast genetic diversity and variation in Single Nucleotide Proteins (SNPs) including deletion, substitution and insertions. All isolates appeared to be highly polymorphic. Conclusion: Detection of Plasmodium species with nested PCR is effective way to identify the individual Plasmodium species and mix infection in low parasitemia for proper treatment option. The phylogenic studies and bio informative tools are reliable methods to identify the relatedness of human malarial parasites and zoonotic e.g. P. knowlesi.